Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-61619-6
|View full text |Cite
|
Sign up to set email alerts
|

Eye contact boosts the reflexive component of overt gaze following

Abstract: Establishing eye contact with an individual can subsequently lead to a stronger gaze-mediated orienting effect. However, studies exploring this phenomenon have, so far, only assessed manual responses and focused on covert attention -namely, without eye movements. Here, in two experiments, we explored for the first time whether eye contact can also impact on overt attention in an oculomotor task. This approach has two main advantages, in that it relies on more sensitive, online measures of attention allocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 58 publications
(96 reference statements)
5
30
0
Order By: Relevance
“…As a main result, smaller latencies and a greater accuracy typically emerge on trials in which the instruction cue and the distracting face share the same spatial vectors (e.g., right-right; i.e., a congruent condition) rather than the opposite (e.g., right-left; an incongruent condition), thus indicating that averted eye-gaze stimuli can interfere with oculomotor planning and execution pervasively. Outcomes similar to those reported by Ricciardelli et al (2002) have been documented in subsequent studies employing different types of facial stimuli (e.g., Ciardo, Marino, Actis-Grosso, Rossetti, & Ricciardelli, 2014;Dalmaso, Alessi, Castelli, & Galfano, 2020a;Dalmaso, Galfano, & Castelli, 2015;Porciello, Liuzza, Minio-Paluello, Caprara, & Aglioti, 2016) but also when directional arrows were employed instead of averted-gaze faces (e.g., Kuhn & Benson, 2007;Kuhn & Kingstone, 2009), in line with a rich stream of studies that reported similar attentional effects for both gaze and arrow stimuli in healthy individuals (e.g., Galfano et al, 2012;Hermens & Walker, 2010;Kuhn & Benson, 2007;Kuhn & Kingstone, 2009;Tipples, 2008).…”
Section: Introductionsupporting
confidence: 78%
“…As a main result, smaller latencies and a greater accuracy typically emerge on trials in which the instruction cue and the distracting face share the same spatial vectors (e.g., right-right; i.e., a congruent condition) rather than the opposite (e.g., right-left; an incongruent condition), thus indicating that averted eye-gaze stimuli can interfere with oculomotor planning and execution pervasively. Outcomes similar to those reported by Ricciardelli et al (2002) have been documented in subsequent studies employing different types of facial stimuli (e.g., Ciardo, Marino, Actis-Grosso, Rossetti, & Ricciardelli, 2014;Dalmaso, Alessi, Castelli, & Galfano, 2020a;Dalmaso, Galfano, & Castelli, 2015;Porciello, Liuzza, Minio-Paluello, Caprara, & Aglioti, 2016) but also when directional arrows were employed instead of averted-gaze faces (e.g., Kuhn & Benson, 2007;Kuhn & Kingstone, 2009), in line with a rich stream of studies that reported similar attentional effects for both gaze and arrow stimuli in healthy individuals (e.g., Galfano et al, 2012;Hermens & Walker, 2010;Kuhn & Benson, 2007;Kuhn & Kingstone, 2009;Tipples, 2008).…”
Section: Introductionsupporting
confidence: 78%
“…We can interpret our results as in line with this idea, since the experimental task of discriminating target letters did not induce the participants to consider trustworthiness and dominance of face stimuli as relevant features for the task itself. It is also worth noting that previous studies reported modulations of the gaze cueing effect related to the features of the paradigms, which presented different stimulus categories intermixed across trials or separated in blocked conditions (Dalmaso, Alessi, et al, 2020; Pavan et al, 2011; Zhao et al, 2014). In our experiments, stimuli varying in two social dimensions (i.e., high/low dominance and trustworthiness) were randomly presented across trials, and this could have reduced the impact of social traits on attention orienting.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, adds to a growing body of evidence showing that gaze cueing is not entirely automatic, in that it does not invariably occur, but can be heavily modulated by social variables (Cohen et al ., 2017; Dalmaso et al ., 2020b). This influence, however, tends to be particularly strong when social variables are made salient by the specific experimental context (see, e.g., Dalmaso et al ., 2020a; Pavan et al ., 2011; Weisbuch et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Since the end of the past millennium, researchers have attempted to explore the attentional orienting response elicited by averted gaze stimuli and developed the so‐called gaze‐cueing paradigm (see Driver et al ., 1999; Friesen & Kingstone, 1998; Hietanen, 1999; Langton & Bruce, 1999). This has proved as an extremely popular paradigm largely because of its flexibility and potential for providing insightful answers in many different fields within psychological science, including social, developmental, and comparative psychology (e.g., Bayliss & Tipper, 2005; Carraro et al ., 2017; Chen & Zhao, 2015; Ciardo, Ricciardelli, Lugli, Rubichi, & Iani, 2015; Dalmaso, Alessi, Castelli, & Galfano, 2020a; Deaner, Shepherd, & Platt, 2006; Farroni, Massaccesi, Pividori, & Johnson, 2004; Marotta et al ., 2014, 2018; Pickron, Fava, & Scott, 2017; Shepherd, 2010).…”
mentioning
confidence: 99%